PENGARUH PENERAPAN CORPORATE GOVERNANCE, LEVERAGE, ROA, DAN UKURAN PERUSAHAAN PADA PENGHINDARAN PAJAK - Darmawan, I Gede Hendy; Sukartha, I Made (E-Jurnal Akuntansi; Vol 9 No 1 (2014), 2014)
Taxes are compulsory contributions from tax subject and addressed to the state. Companies subject to tax as one that contributes the most in state tax revenue. Corporate taxation is a burden that can reduce corporate profits, while tax revenue for the state is to be used to fund governance . The difference is what causes the interests of the company to manage the tax burden, both legally and illegally. Tax avoidance is one way companies manage their tax burden legal. Indonesian state tax ratio smaller than average medium- country tax rate shows that the government has not been able to optimally absorb the revenue derived from taxation and tax avoidance activity is indicated by the company in Indonesia. Factors that may indicate the presence of corporate tax avoidance activity should be observed both by investors and regulators. To determine the effect of corporate governance, leverage, return on assets (ROA), and the size of the company partially on tax evasion is the purpose of this study. Companies listed on the Indonesia Stock Exchange and included in the 2010-2012 period CGPI rank numbering 55 companies sampled in this study. Tax evasion can be measured by the difference between commercial income with taxable income then the total assets of the company are used as a divider. The results showed that there are significant between Corporate Governance , ROA, and the size of the company with tax avoidance. Leverage variable in this study showed no effect on tax evasion .
Keywords: Tax Avoidance, Corporate Governance, Return on Assets, company size